The trait of schadenfreude and its relationship to self-esteem among university students - Hawra Haider Muhammad Al-Jabri, Lect. Dr. (lark, 2025)
The current research aims at the trait of schadenfreude and its relationship with self-esteem among university students to :-1-Identify the schadenfreude trait among university students.2- Identify the self-esteem of university students .3- There is a significant difference at the level of significance (0.05) in the schadenfreude trait among university students according to the gender variable (male – female).4- there is no significant difference at the level of significance (0.05) in self - esteem among university students according to the gender variable (male-female).5-identify the nature of the relationship between schadenfreude and self-esteem among university students.In order to achieve the research objectives, the researcher translated the schadenfreude scale according to the theory of van Dijk et al . (2011) and adopted the self-esteem scale, extracted the statistical characteristics of the two scales (distinction, paragraph difficulty, validity and reliability) after analyzing the data statistically, the research  concluded the following results:-1-university students are not characterized by schadenfreude .2-university students are characterized by high esteem.3-there are a significant difference in the schadenfreude trait depending on the gender variable and in favor of males, that is, they are more schadenfreude than females.4-there are no significant difference in self-esteem depending on the gender variable, i.e. there is no difference between males and females in self-esteem .5-there is an inverse relationship between schadenfreude and self-esteem, as low self-esteem is associated with schadenfreude,  the higher the student's score on the schadenfreude scale, the lower his score on the self-esteem scale, and vice versa, if the lower the degree of schadenfreude, the higher the degree of self-esteem Based on these results, a set of recommendations and proposals was made.
Keywords: schadenfreude, self-esteem, low self-esteem, high self-esteem..